The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
All Days 2008
DOI: 10.2118/112793-ms
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Chemical EOR Pilot Strategy for a Complex, Low Permeability Water Flood

Abstract: A screening study and subsequent chemical EOR application pilot strategy for a complex, low-permeability waterflood is presented. Our focus has been on developing appropriate field application options allowing flexibility of operation against a background of reservoir complexity and uncertainty. Australia's Barrow Island Windalia reservoir, the nation's largest onshore waterflood, was developed in the late 1960's. Cumulative oil production to date is approximately 288 MMSTBO. Planning a chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Despite the volatility of oil prices, it is fair to conclude that operators are showing a growing interest on chemical EOR flooding. This trend is also supported by the increase of screening studies to evaluate or re-estimate the EOR potential of chemical flooding in different basins (Alvarado et al 2008;Costa et al 2008;Fletcher and Morrison, 2008;.…”
Section: Chemical Eor In Sandstone Reservoirsmentioning
confidence: 76%
“…Despite the volatility of oil prices, it is fair to conclude that operators are showing a growing interest on chemical EOR flooding. This trend is also supported by the increase of screening studies to evaluate or re-estimate the EOR potential of chemical flooding in different basins (Alvarado et al 2008;Costa et al 2008;Fletcher and Morrison, 2008;.…”
Section: Chemical Eor In Sandstone Reservoirsmentioning
confidence: 76%
“…For example, the laboratory evaluation of Windalia polymer flood reported the emulsion formation tendencies between the reservoir oil and different injection brines. Fletcher and Morrison (2008) reported in their study that higher salinity (TDS = 38,000 ppm) brine showed less emulsification tendencies than lower salinity (TDS = 29,000 ppm) injection brine. However, it is not clear if high polymer retention (≥130 mg/g of rock) and RRF (8 to 45) values reported in this study are due to low permeability (1.0 -13.8 mD) of the reservoir core plugs used and/or the emulsification of oil-waterpolymer in-situ during the corefloods.…”
Section: Summary Discussionmentioning
confidence: 93%
“…Windalia field (Fletcher and Morrison, 2008;Haynes, Clough, Fletcher &Weston, 2013) is a high clay content sandstone and low permeability light oil (36°API) reservoir (65°C) in Australia. Windalia reservoir has an OOIP of 819 MMbbls and it is under line-drive water injection since 1967 reporting a recovery factor of 37%.…”
Section: Polymer Injection Ratesmentioning
confidence: 99%
“…Therefore and despite the volatility of oil prices, it is fair to conclude that operators and surfactant manufacturers are showing a growing interest in EOR chemical flooding [132,133]. This trend is also noticed with an increase of screening and lab studies to evaluate or re-estimate EOR potential of chemical flooding in different basins [134][135][136][137][138][139][140][141].…”
Section: Chemical Methodsmentioning
confidence: 99%